DESCRIPTION OF THE INCIDENCE OF POST OPERATIVE NAUSEA AND VOMITING (PONV) IN CURETTAGE SURGERY PATIENTS - Siti Mirhalina Hasibuan; Wahyu Adi Pratama (Jurnal Kesehatan, 2023)
Symptoms that often appear troublesome after surgery and anesthesia are pain and vomiting. The prevalence of PONV is very high and difficult for patients and can be detrimental during the recovery process after surgery. Nausea and vomiting are the most common adverse events in patients with a probability of 30% in the population undergoing surgery and up to 80% in the high-risk group. This study aims to determine the picture of the incidence of PONV in curettage patients who are carried out under general anesthesia TIVA at Vita Insani Hospital. This study used an analytical descriptive method with a cross-sectional approach. The population used in this sample was patients who carried out curettage procedures and were given general anesthesia TIVA at Vita Insani Hospital in July-September 2021. The results of the study on the Chi-square test obtained a p-value based on smoking history 0.014, based on age 0.693, based on diagnosis of 0.802, and based on additional ketamine 0.401 drugs. There was an association of PONV with smoking history, no association of PONV with age and diagnosis, and no association of PONV with additional ketamine drugs.